CX3CL1 and its receptor CX3CR1 interact with RhoA signaling to induce paclitaxel resistance in gastric cancer - Xiangyang Liu; Zhonghui Yu; Yun Li; Junzi Huang (Heliyon, 2024)
C-X3-C motif chemokine ligand 1 (CX3CL1) is a transmembrane protein, and the membranal and soluble forms of CX3CL1 exhibit different functions, although both bind to the CX3CR1 chemokine receptor. The CX3CL1/CX3CR1 axis induces many cellular responses relevant to cancer, such as proliferation, migration, invasion, and apoptosis resistance. Here we attempt to elucidate whether CX3CL1/CX3CR1 is associated with paclitaxel (PTX) resistance in gastric cancer (GC). The Gene Expression Omnibus database was queried to screen for differentially expressed genes in GC cells caused by drug resistance, and CX3CL1 was selected as a candidate. CX3CL1 was overexpressed in PTX-resistant cells and tissues. CX3CL1 loss sensitized GC cells to PTX, promoted apoptosis and DNA damage, and inhibited cell proliferation, migration, and invasion. CX3CR1 reversed the ameliorative effect of CX3CL1 silencing on PTX sensitivity in GC cells. The promotion of PTX resistance by CX3CL1/CX3CR1 was inhibited by impairment of the small GTPase Ras homolog gene family member A (RhoA) pathway in vitro and in vivo. These findings indicate that the CX3CL1/CX3CR1 expedites PTX resistance through the RhoA signaling in GC cells.